CD 122 - Bread wheat, suitable for cultivation across southern Brazil - Franco,Francisco de Assis (2014)
The cultivar CD 122 was tested in the wheat-producing regions VCU 1, 2 and 3, with an average grain yield of 3,527 kg ha-1 when fungicide-treated, exceeding the average of the control cultivars by 5%. CD 122 is resistant to leaf rust and was classified as bread wheat.